Development of a recombinant human ovarian (BG1) cell line containing estrogen receptor α and β for improved detection of estrogenic/antiestrogenic chemicals. (9th December 2015) - Brennan, Jennifer C.; Bassal, Arzoo; He, Guochun; Denison, Michael S.
Abstract: Estrogenic endocrine‐disrupting chemicals are found in environmental and biological samples, commercial and consumer products, food, and numerous other sources. Given their ubiquitous nature and potential for adverse effects, a critical need exists for rapidly detecting these chemicals. The authors developed an estrogen‐responsive recombinant human ovarian (BG1Luc4E2) cell line recently accepted by the US Environmental Protection Agency (USEPA) and Organisation for Economic Co‐operation and Development (OECD) as a bioanalytical method to detect estrogen receptor (ER) agonists/antagonists. Unfortunately, these cells appear to contain only 1 of the 2 known ER isoforms, ERα but not ERβ, and the differential ligand selectivity of these ERs indicates that the currently accepted screening method only detects a subset of total estrogenic chemicals. To improve the estrogen screening bioassay, BG1Luc4E2 cells were stably transfected with an ERβ expression plasmid and positive clones identified using ERβ‐selective ligands (genistein and Br‐ERβ‐041). A highly responsive clone (BG1LucERβc9) was identified that exhibited greater sensitivity and responsiveness to ERβ‐selective ligands than BG1Luc4E2 cells, and quantitative reverse‐transcription polymerase chain reaction confirmed the presence of ERβ expression in these cells. Screening of pesticides and industrial chemicals identified chemicals that preferentially stimulated ERβ‐dependent reporter gene expression. Together, these results not only demonstrate the utility of this dual‐ER recombinant cell line for detecting a broader range of estrogenic chemicals than the current BG1Luc4E2 cell line, but screening with both cell lines allows identification of ERα‐ and ERβ‐selective chemicals. Environ Toxicol Chem 2016;35:91–100. © 2015 SETAC